Ayurvedic Management of Hyper Emesis Gravidarum - Keerthy Krishnakumar; Meera Nair N (International Journal of Ayurveda and Pharma Research, 2025)
Hyperemesis gravidarum is a severe type of vomiting of pregnancy which has got deleterious effect on the health of mother and/or incapacitates her in day-to- day activities. The incidence of Hyperemesis gravidarum ranges from 0.3 to 3%. Garbhini chardi is one among the Vyaktha garbha lakshanas. Due to Garbha peeda, Duhrida avamanana causes Kapha pitha dushti leading to Vatadushti along with Agnimandhya, Dosha utklesha and thus results in the expulsion through the mouth. A multipara with amenorrhea for 7 weeks 5 days presenting with severe vomiting, fatigue, constipation came to our OPD was assessed with PUQE- 24 scale and was managed with Ayurvedic treatment.